For Whom (and When) the Time Bell Tolls: Chronotypes and the Synchrony Effect. - May, Cynthia P.; Hasher, Lynn; Healey, Karl (Perspectives on Psychological Science, 2023)
Circadian rhythms are powerful timekeepers that drive physiological and intellectual functioning throughout the day. These rhythms vary across individuals, with morning chronotypes rising and peaking early in the day and evening chronotypes showing a later rise in arousal, with peaks in the afternoon or evening. Chronotype also varies with age from childhood to adolescence to old age. As a result of these differences, the time of day at which people are best at attending, learning, solving analytical problems, making complex decisions, and even behaving ethically varies. Across studies of attention and memory and a range of allied areas, including academic achievement, judgment and decision-making, and neuropsychological assessment, optimal outcomes are found when performance times align with peaks in circadian arousal, a finding known as the synchrony effect. The benefits of performing in synchrony with one's chronotype (and the costs of not doing so) are most robust for individuals with strong morning or evening chronotypes and for tasks that require effortful, analytical processing or the suppression of distracting information. Failure to take the synchrony effect into consideration may be a factor in issues ranging from replication difficulties to school timing to assessing intellectual disabilities and apparent cognitive decline in aging.